Antioxidant activity in crude petroleum benzene, chloroform, methanol and water extracts of six selected vegetables - Sumathi Murti,; Nurhayati Zainal Abidin,; Ashril Yusof, (Universiti Kebangsaan Malaysia, 2013)
In this study, crude petroleum benzene, chloroform, methanol and water extracts of six selected vegetables namely, garlic chives (Allium tuberosum), celery (Apium graveolens (L.)), sweet potato leaves (Ipomoea batatas (L.)), curry leaves (Murraya koenigii (L.)), winged beans (Psophocarpus tetragonolobus) and sweet leaves (Sauropus androgynus) were tested for antioxidant activities using three bioassays namely 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, reducing power assay and metal chelating assay. Overall, among the 24 crude extracts tested, petroleum benzene and chloroform extract of Murraya koenigii (L.) showed higher free radical scavenging activities (IC50 = 0.02 mg/mL and 0.0225 mg/mL, respectively) when compared to ascorbic acid (IC50 = 0.00375 mg/mL) and strong reducing powers with absorbance value of 1.208 ± 0.006 and 1.833 ± 0.003 when compared to butylated hydroxyanisole with absorbance value of 2.625 ± 0.004 at the highest concentration tested, 1 mg/mL in both DPPH and reducing power assay, respectively. In metal chelating assay, methanol, petroleum benzene and chloroform extracts of Murraya koenigii (L.) showed moderate metal chelating activities of 88.60 ± 0.02%, 78.30 ± 0.23% and 73.61 ± 0.22%, respectively, at 1 mg/mL when compared to ethylenediaminetetraacetic acid which is 98.63 ± 0.13%. These findings suggested the important significance of Murraya koenigii (L.) consumption in prevention of diseases.